Phenology, Canopy Aging and Seasonal Carbon Balance as Related to Delayed Winter Pruning of Vitis vinifera L. cv. Sangiovese Grapevines - Gatti, Matteo; Pirez, Facundo J.; Chiari, Giorgio; Tombesi, Sergio; Palliotti, Alberto; Merli, Maria C.; Poni, Stefano (Frontiers in Plant Science, 2016)
Manipulating or shifting annual grapevine growing cycle to offset limitations imposed by global warming is a must today, and delayed winter pruning is a tool to achieve it. However, no information is available about its physiological background, especially in relation to modifications in canopy phenology, demography and seasonal carbon budget. Mechanistic hypothesis underlying this work was that very late winter pruning can achieve significant postponement of phenological stages so that ripening might occur in a cooler period and, concurrently, ripening potential can be improved due to higher efficiency and prolonged longevity of the canopy. Variability in the dynamics of the annual cycle was created in mature potted cv. Sangiovese grapevines subjected to either standard winter pruning (SWP) or late and very late winter pruning (LWP, VLWP) performed when apical shoots on the unpruned canes were at the stage of 2 and 7 unfolded leaves. Vegetative growth, phenology and canopy net CO2 exchange (NCER) was followed throughout the season. Despite LWP and VLWP induced a bud-burst delay of 17 and 31 days vs. SWP, the delay was fully offset at harvest for LWP and was reduced to 6 days in VLWP. LWP showed notably higher canopy efficiency as shorter time needed to reach maximum NCER/leaf area (22 days vs 34 in SWP), highest maximum NCER/leaf area (+37% as compared to SWP) and higher NCER/leaf area rates from veraison to end of season. As a result, seasonal cumulated carbon in LWP was 17% higher than SWP. A negative functional relationship was also established between amount of leaf area removed at winter pruning and yield per vine and berry number per cluster. Although retarded winter pruning was not able to postpone late-season phenological stages under the warm conditions of this study, it showed a remarkable potential to limit yield while improving grape quality, thereby fostering the hypothesis that it could be used to replace time-consuming and costly cluster thinning. This preliminary study indicates that proper winter pruning date should be timed so as not to exceed the stage of two unfolded leaves.